Empires of exceptionalism: Lessons from the EU AI Act and attempts at AI legislation in California - Hosuk Lee-Makiyama; Claudia Lozano Rodriguez (European Centre for International Political Economy (ECIPE), 2024)
The EU AI Act, which passed after three years of negotiations and much ambivalence, sets a comprehensive regulatory framework that reflects the European Union's unique needs that are not translatable to other jurisdictions. The proposed bill in California (SB 1047) illustrates this case in point. The bill could potentially mislead the public into thinking that AI is already under effective regulatory control. Lawmakers must recognize that the EU differs from other systems. The EU AI Act is not only shaped by the desire to slow down global AI development, allowing Europe to catch up with rivals like the US and China: The EU lacks an enforceable constitution, and the Act prohibits its governments to impose social scoring and discriminatory measures. SB 1047 only addressed humanity-ending disasters and had unclear practical value. Meanwhile, the EU AI Act was passed into law to prevent internal competition and Europe's history of authoritarianism. Existing laws in California and the EU already regulate most AI use cases. In addition, the EU AI Act reviews existing regulations to ensure they are still fit for purpose, something California failed to do in SB 1047. A critical takeaway is to examine existing obligations or executive powers (including enforcement agencies and public funding) to achieve the desired policy objectives. The diverging outcomes of the two laws show the importance of avoiding mismatches between policy objectives and legislative scope. AI regulation cannot substitute for other policy objectives, like privacy and antitrust. Also, lawmakers must weigh the cost of failed regulation against the risks of non-regulation. California did not see any immediate costs of inaction, whereas delayed action by the EU might have led to the fragmentation of its internal market. Also, given its collective decision-making, the EU can escape accountability for policy failures due to premature laws in a way the leaders in other political systems cannot.
Keywords: 330